2016
DOI: 10.1016/j.drugalcdep.2016.03.026
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive and emotional impairments in adults with attention-deficit/hyperactivity disorder and cocaine use

Abstract: BACKGROUND: Attention-deficit/hyperactivity disorder (ADHD) is an important modulator of cognitive and social functioning in cocaine addiction but it is unclear whether ADHD symptoms and cocaine use display mutually aggravating interaction effects on cognition, social functioning, and depressive symptoms. Therefore, we investigated the interaction of cocaine use and adult ADHD on social and non-social cognition and depressive symptoms. METHODS: Twenty-four cocaine users with (CU+ADHD) and 30 without ADHD (CU-A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
24
0
2

Year Published

2017
2017
2020
2020

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(30 citation statements)
references
References 73 publications
4
24
0
2
Order By: Relevance
“…Our results indicate that mothers with adequate to high PRF had significantly higher cognitive flexibility capacities compared to mothers with negative to low PRF. These results support studies that have found deficits in perspective taking to be negatively related to cognitive flexibility (Carlson et al, 2015;Stuss & Knight, 2002;Wunderli, Vonmoos, Niedecker, Hulka, Preller et al, 2016). Individuals easily distracted by stimuli have been found to exhibit deficits in attributing complex emotional and motivational states to others (Decety & Sommerville, 2003).…”
Section: Prfsupporting
confidence: 85%
“…Our results indicate that mothers with adequate to high PRF had significantly higher cognitive flexibility capacities compared to mothers with negative to low PRF. These results support studies that have found deficits in perspective taking to be negatively related to cognitive flexibility (Carlson et al, 2015;Stuss & Knight, 2002;Wunderli, Vonmoos, Niedecker, Hulka, Preller et al, 2016). Individuals easily distracted by stimuli have been found to exhibit deficits in attributing complex emotional and motivational states to others (Decety & Sommerville, 2003).…”
Section: Prfsupporting
confidence: 85%
“…• The prevalence of adult ADHD in chronic cocaine users is higher than in the general population (Wunderli et al, 2016).…”
Section: Key Facts Of Attention-deficit/hyperactivity Disordermentioning
confidence: 98%
“…Given that cocaine use is frequently associated with symptoms of attention-deficit hyperactivity disorder (ADHD) (Wilson, 2007) and depression (Swendsen & Merikangas, 2000), it should be noted that both co-morbidities are also important modulators of cognitive functioning in cocaine users (Vonmoos et al, 2013). Recent research studies found that the combination of ADHD and cocaine consumption seemed to have a cumulative aggravation of detrimental effects on cognitive performance (Vonmoos et al, 2013;Wunderli et al, 2016). By contrast, only a weak additive impact of depressive symptoms on cognitive performance was found in recreational users, but not in dependent users (Vonmoos et al, 2013).…”
Section: Confounding and Moderating Factorsmentioning
confidence: 99%
“…In addition, we also aimed to precisely investigate the effects of demographic, cognitive, psychopathological, and substance use severity on the sensitivity gain, loss, and risk information. Hence, based on previous studies that indicate that self-reported impulsivity and gambling behaviour are strongly state-dependent in CU [37], and that the often comorbid symptoms of an attention deficit hyperactivity disorder (ADHD) aggravates the effects of cocaine use on cognitive impairment [38,39], we expect that both trait impulsivity and ADHD symptoms would reduce sensitivity to gain, loss, and risk information in CU. In sum, we investigate how chronic cocaine use, as well as demographic, clinical, and cognitive factors, affect sensitivity to gain, loss, and risk information in value-based decisions.…”
Section: Introductionmentioning
confidence: 99%